Injectable and Conductive Granular Hydrogels for 3D Printing and Electroactive Tissue Support. Issue 20 (21st August 2019) - Shin, Mikyung; Song, Kwang Hoon; Burrell, Justin C.; Cullen, D. Kacy; Burdick, Jason A.
Abstract: Conductive hydrogels are attractive to mimic electrophysiological environments of biological tissues and toward therapeutic applications. Injectable and conductive hydrogels are of particular interest for applications in 3D printing or for direct injection into tissues; however, current approaches to add conductivity to hydrogels are insufficient, leading to poor gelation, brittle properties, or insufficient conductivity. Here, an approach is developed using the jamming of microgels to form injectable granular hydrogels, where i) hydrogel microparticles (i.e., microgels) are formed with water‐in‐oil emulsions on microfluidics, ii) microgels are modified via an in situ metal reduction process, and iii) the microgels are jammed into a solid, permitting easy extrusion from a syringe. Due to the presence of metal nanoparticles at the jammed interface with high surface area in this unique design, the granular hydrogels have greater conductivity than non‐particle (i.e., bulk) hydrogels treated similarly or granular hydrogels either without metal nanoparticles or containing encapsulated nanoparticles. The conductivity of the granular hydrogels is easily modified through mixing conductive and non‐conductive microgels during fabrication and they can be applied to the 3D printing of lattices and to bridge muscle defects. The versatility of this conductive granular hydrogel will permit numerous applications where conductive materials are needed. Abstract : Injectable and conductive granular hydrogels are introduced through the jamming of microgels containing gallol redox chemistry inspired by fruit browning phenomena, coupled with an in situ metal reduction process. The conductive hydrogels provide facile 3D printability with desirable conductivity of extruded filaments, as well as electrical tissue conduction for further biomedical applications related to electroactive tissues.